ANALISIS KINERJA KEUANGAN PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Khasanah, Putri Lutfiyatul; C. Tri Widiastuti; Rita Meiriyanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of financial ratios on the financial performance of banking institutions listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The research is based on the crucial role of banking financial performance in maintaining national financial stability, especially during the post-pandemic recovery period. A descriptive quantitative approach with an associative analysis method was employed to examine the relationships among variables using numerical data from banking financial ratios. Multiple linear regression analysis was applied to five independent variables Current Ratio (CR), Operating Expenses to Operating Income (BOPO), Profit margin (PM), Return on Equity (ROE), and Debt to Asset Ratio (DAR) with Return on Assets (ROA) as the dependent variable. The findings show that BOPO has a significant negative effect on ROA, while PM, ROE, and DAR have significant positive effects, and CR shows no significant effect. These results indicate that operational efficiency, profitability, and leverage are the dominant factors influencing banking financial performance. Future researchers are encouraged to include variables such as Non-Performing Loan (NPL), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), and bank size, as well as adopt panel regression or SEM methods for more comprehensive and in-depth results.